2022
DOI: 10.1021/acscatal.2c05862
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hydrophobic Single-Atom Catalyst with Flexible Sulfur Motif for Aqueous-Phase Hydrogenative Transformation

Abstract: Metalloenzyme-like metal–nitrogen–carbon (M–N–C) single-atom catalysts (SACs) have received increasing attention in the synthesis of fine chemicals because of the abundant atomic sites and versatile catalytic properties. However, the organic transformations with high atom efficiency over SACs in aqueous media were less investigated. Inspired by the hydrophobic pockets of the metalloenzyme, herein we introduced a hydrophobic, atomically dispersed Pd catalyst (Pd1–S–C) in the sulfur-doped carbon based on metal–s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…[ 25 ] To further uncover the important roles of H 2 O 2 in improving the photocatalytic CO 2 reduction reaction, the diffusion behaviors of the CO 2 gas in the two different systems, pure H 2 O ( Figure a) and the mixture solution of 5% H 2 O 2 ‐H 2 O (Figure 7b), were performed using the molecular dynamics (MD) simulation. [ 26 ] Mean‐squared displacement (MSD) analysis of the CO 2 gas movement (Figure 7c) indicated that the calculated CO 2 diffusion coefficient (DC, 0.787 cm 2 s −1 ) in the mixture solution system of 5% H 2 O 2 ‐H 2 O was greater than in the pure H 2 O system (0.525 cm 2 s −1 ). The result revealed that H 2 O 2 around the TBHO surface created a unique microenvironment, favored CO 2 gas diffusion in the reaction medium, which might provide an advantage to enhance the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] To further uncover the important roles of H 2 O 2 in improving the photocatalytic CO 2 reduction reaction, the diffusion behaviors of the CO 2 gas in the two different systems, pure H 2 O ( Figure a) and the mixture solution of 5% H 2 O 2 ‐H 2 O (Figure 7b), were performed using the molecular dynamics (MD) simulation. [ 26 ] Mean‐squared displacement (MSD) analysis of the CO 2 gas movement (Figure 7c) indicated that the calculated CO 2 diffusion coefficient (DC, 0.787 cm 2 s −1 ) in the mixture solution system of 5% H 2 O 2 ‐H 2 O was greater than in the pure H 2 O system (0.525 cm 2 s −1 ). The result revealed that H 2 O 2 around the TBHO surface created a unique microenvironment, favored CO 2 gas diffusion in the reaction medium, which might provide an advantage to enhance the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…In this material, Pd single atoms were coordinated by sulfur, and the catalyst was used to perform semihydrogenation of alkynes to alkenes in water (Scheme 35). [74] The catalyst showed excellent reactivity and selectivity towards the alkenes, ca. >90 % over alkane byproducts.…”
Section: Thermally Driven Organic Synthesis Using Sacsmentioning
confidence: 99%
“…The charge configuration of active site can directly affect the adsorption and desorption of reactants, thus changing the reaction energy barrier. The superior catalytic performance of SACs has been achieved by adjusting charge configurations [66][67][68][69]. Among them, the introduction of a second metal atom to construct a dual metal pair active site has been proved as a promising way to realized desired charge configurations for various reactions [70,71].…”
Section: Alteration Of the Charge Configuration Of The Active Sitementioning
confidence: 99%